IMPLICATION OF GOOD CORPORATE GOVERNANCE ON PT. NI - Pamuji, Endang (Dinasti International Journal of Digital Business Management, 2020)
Companies that have roles in the pharmaceutical field that are discussed in the health world and are related to direct consumers or indirect consumers, business partners, distributors, and so on. Good Corporate Governance, namely, processes, policies, rules, and policies that affect the direction, management, and control of a company or company. PT.NI. Having business goals that are not just looking for profit but also have social responsibility and assistance in the internal and external environment (human, animal, plant and environment).